EKKLESIA DI RUANG PUBLIK: PEMBACAAN EKLESIOLOGIS ATAS MATIUS 16:18 DALAM KONTEKS GEREJA INDONESIA - Heintje Barry Kobstan; Jonathan Pattiasina (STT Bethel Indonesia Jakarta, 2025)
When disease begins to infect the entire body of a Christian, Christians try various ways to restore and heal their body to health again, but human methods are limited, the disease remains in the human body, so that severe self-doubt makes people feel very hopeless in living life and looking to their future, as if there is no more hope for recovery and returning to a healthy life. Therefore, the current research aims to inform when medical treatment does not change the human body to be healed, so that spiritual treatment appears to be able to provide peace and guarantee of healing as long as the person fully believes in the Healing Power of God by having faith as big as a mustard seed, then total Divine Healing can occur in the human body. This qualitative research shows the role and implications of Christian belief and having faith as big as a mustard seed, the power of prayer, the power of praise and worship, in total healing of all illnesses. A person's disbelief that their illness will be healed when someone believes that by paying attention to a healthy lifestyle, diligently controlling their health regularly and placing true trust in hope in God as Jenovah Rapha and eternal salvation for Christians. The discussion in the research now explains that as long as Christians believe in the power of healing, singing and psalming to God will awaken faith the size of a mustard seed in Christians for total divine healing for all their illnesses, finally it can be concluded that total healing for all human illnesses, especially Christians, is by strengthening the Christian's faith from having no hope to having faith the size of a mustard seed, having hope for complete recovery and having hope again in the future for the glory of God.